Teaching Task Scheduling as Multivariable Cascade Control. Issue 6 (2016) - Leva, Alberto; Terraneo, Federico
Abstract: This paper presents a didactic activity belonging to a long-term project, aimed at complementing the culture of computer engineering students with a solid knowledge of systems and control theory and methods. The use of control to govern and optimise the behaviour of computing systems is felt in the computer engineering community as a necessity. The proposed activity – that refers to task scheduling – responds to this need, guiding the necessary cultural enrichment and avoiding possible errors and misinterpretations, so as to foster a deeper cooperation of the computer and the control communities.